Synthesis of Ultrathin Topological Insulator β‐Ag2Te and Ag2Te/WSe2‐Based High‐Performance Photodetector. Issue 2 (18th November 2022) - Sun, Fapeng; Hong, Wenting; He, Xu; Jian, Chuanyong; Ju, Qiankun; Cai, Qian; Liu, Wei
Abstract: β‐Ag2 Te has attracted considerable attention in the application of electronics and optoelectronics due to its narrow bandgap, high mobility, and topological insulator properties. However, it remains a significant challenge to synthesize 2D Ag2 Te because of the non‐layered structure of Ag2 Te. Herein, the synthesis of large‐size, ultrathin single crystal topological insulator 2D Ag2 Te via the van der Waals epitaxial method for the first time is reported. The 2D Ag2 Te crystal exhibits p‐type conduction behavior with high carrier mobility of 3336 cm 2 V −1 s −1 at room temperature. Taking advantage of the high mobility and perfect electron structure of Ag2 Te, the Ag2 Te/WSe2 heterojunctions are fabricated via mechanical stacking and show an ultrahigh rectification ratio of 2 × 10 5 . Ag2 Te/WSe2 photodetector also exhibits self‐driven properties with a fast response speed (40 µs/60 µs) in the near‐infrared region. High responsivity (219 mA W −1 ) and light ON/OFF ratio of 6 × 10 5 are obtained under the photovoltaic mode. The overall performance of the Ag2 Te/WSe2 photodetector is significantly competitive among all reported 2D photodetectors. These results indicate that 2D Ag2 Te is a promising candidate for future electronic and optoelectronic applications. Abstract : Using van der Waals epitaxial method, ultrathin topological insulator Ag2 Te single crystals are synthesized. The Ag2 Te single crystals exhibit p‐type conduction behavior with high carrier mobility of 3336 cm 2 V –1 s –1 at room temperature. A self‐driven broad‐spectrum high‐performance photodetector with high responsivity, high on/off ratio, and fast response speed is obtained based Ag2 Te/WSe2 heterojunction.